The memphis police strike: A retrospective analysis - Giacopassi, D. J. (American journal of criminal justice, 1981)
Previous studies of police strikes take a narrow perspective. with regard to both the causes and consequences of the job action. The present case. study attempts to put the Memphis police steike of 7978 in historical perspective by viewing the antecedent conditions as important to an understanding of why the police. struck. Kdditionally, the article attempts to determine-the Auccess or failure Of the. strike by examining the long term cons equences of the strike on both the Memphis Police Department and the Memphis Police Asso ciation, the official bargaining agent of the rank and file members of the M. P. D.